2022
DOI: 10.3390/foods11030392
|View full text |Cite
|
Sign up to set email alerts
|

Zizania latifolia Cell Wall Polysaccharide Metabolism and Changes of Related Enzyme Activities during Postharvest Storage

Abstract: The metabolism of polysaccharides in the Zizania latifolia cell wall helps maintain the postharvest quality during storage. Fresh Z. latifolia was stored at 4 °C and 25 °C to evaluate the hardness, cell wall polysaccharide composition, cell wall structure, active ingredients, and cell wall metabolism-related enzyme activities. The results showed that hardness declined concomitantly with an increase in water-soluble pectin content during storage, as well as with a decrease in propectin and cellulose contents. C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 42 publications
2
10
0
Order By: Relevance
“…Correlation analysis showed that the lignin content, cellulose content, and SP content were negatively correlated with firmness, while propectin content, PG activity, and, Cx activity, were positively correlated with it (Figure 5). Similar result was also observed by Huang et al (2022) that the hardness was related to SP content. A significant negative correlation between cellulose content and Cx activity was observed, and the correlation coefficient is −0.98 and −0.94 for control group and 9 µl L −1 ozone treated group, respectively (Figure 5).…”
Section: Resultssupporting
confidence: 91%
See 1 more Smart Citation
“…Correlation analysis showed that the lignin content, cellulose content, and SP content were negatively correlated with firmness, while propectin content, PG activity, and, Cx activity, were positively correlated with it (Figure 5). Similar result was also observed by Huang et al (2022) that the hardness was related to SP content. A significant negative correlation between cellulose content and Cx activity was observed, and the correlation coefficient is −0.98 and −0.94 for control group and 9 µl L −1 ozone treated group, respectively (Figure 5).…”
Section: Resultssupporting
confidence: 91%
“…Contrary to the propectin content, the SP accumulated during the storage, and ozone treatment could impede the increase in water bamboo shoots (Figure 2D). The accumulation of SP might due to the hydrolysis of propectin, which was consistent with the previous results (Huang et al, 2022).…”
Section: Effect Of Ozone Treatment On Cell Wall Compositionsupporting
confidence: 93%
“…However, the long-term continuous planting of water oat can lead to the accumulation of pathogenic bacteria, which causes a decrease in the quality of water oat and soil [3]. The existing studies on water oat mostly focus on its yield, quality, storage, and nutritional and healthcare values [2,4] but rarely explore whether the long-term planting of water oat would cause soil degradation and change the soil microbial structures. In this context, studying the changes in the soil environment of water oat with different planting years is of great significance for understanding and evaluating the effect of water oat on soil quality and the sustainable development of water oat.…”
Section: Introductionmentioning
confidence: 99%
“…Softening is a typical ripening feature of banana fruit, mainly brought by the structural breakdown of cell walls, particularly the breakdown of components of polysaccharide compositions including pectin, cellulose and hemicellulose (Vorwerk et al ., 2004). In plant cell walls, pectin covalently combines with cellulose and hemicellulose to form a protective network, which maintains the morphology and integrity of the cell wall (Huang et al ., 2022). In our study, the contents of HSP, NSP, cellulose and hemicellulose decreased to varying degrees over storage, while the content of WSP increased, showing that the softening of banana fruit correlated with the conversion of water‐insoluble pectin to WSP.…”
Section: Discussionmentioning
confidence: 99%